Respiratory Impact of PM10 and PM2.5 Exposure among Furniture Workers in Tegal - Anissah, Neli; Setiani, Onny; Hanani D, Yusniar (Poltekkes Kemenkes Surabaya, 2025)
The furniture industry has a high potential for particulate matter (PM10 and PM2.5) exposure, which may lead to impaired lung function and occupational diseases. Dust from cutting, sanding, and finishing processes can be inhaled and accumulate in the respiratory tract, increasing the risk of respiratory dysfunction. This study aimed to determine the relationship between PM exposure and impaired lung function among furniture industry workers in Tegal Regency. This study was an analytical observational study with a cross-sectional approach involving 100 production workers. PM concentration was measured using the Haz Dust EPAM-5000, and lung function was assessed using spirometry. Bivariate analysis was conducted using the chi-square test, and multivariate analysis was performed using logistic regression. A total of 57% of respondents experienced impaired lung function. Bivariate analysis showed a significant relationship between PM 10 concentration (p=0.001; OR=4.725), PM 2.5 concentration (p=0.007; OR=3.580), inhalable dust concentration (p=0.034; OR=2.478), duration of employment (p=0.003; OR=3.929), and working hours (p=0.001; OR=4.143) with impaired lung function. A total of 57% of respondents experienced impaired lung function, consisting of mild restriction, moderate restriction, and mild obstruction. There was a significant association between PM 10 concentration (p = 0.001), PM 2.5 concentration (p = 0.007), and duration of employment (p = 0.003) with impaired lung function. Logistic regression analysis identified PM 10 concentration as the dominant factor associated with impaired lung function (p = 0.002; OR = 3.976; 95% CI: 1.641–9.637.